Adaptive control of a class of nonlinear systems with fuzzy approximators: an application to longitudinal vehicle control. (2nd April 2009) - Dai, Xiaohui; Li, C.K.; Rad, A.B.
We employ a direct adaptive fuzzy controller that approximates an ideal optimal controller. A linear relationship between approximation error and parameters is established in order to tune all the parameters online. Subsequently, adaptive laws are proposed based on the Lyapunov synthesis approach. The advantage of the proposed method is that the parameters of the consequences of fuzzy rules as well as those of the membership functions are tuned. As a result, a stable and flexible controller is achieved. The performance of the adaptive scheme is demonstrated through the simulation studies of a longitudinal vehicle control system.